Underlying mechanisms of evasion from NK cells as rationale for improvement of NK cell-based immunotherapies - Seliger, Barbara; Koehl, Ulrike (Frontiers in Immunology, 2022)
Natural killer (NK) cells belong to the family of innate immune cells with the capacity to recognize and kill tumor cells. Different phenotypes and functional properties of NK cells have been described in tumor patients, which could be shaped by the tumor microenvironment. The discovery of HLA class I-specific inhibitory receptors controlling NK cell activity paved the way to the fundamental concept of modulating immune responses that are regulated by an array of inhibitory receptors and emphasized to explore the potential of NK cells in cancer therapy. Despite a number of NK cell-based approaches are currently developed, many challenges have to be overcome for improved efficacy of these therapies, such as escape of tumor cells from NK cell recognition due to their expression of inhibitory molecules, immune suppressive signals of NK cells, reduced NK cell infiltration of tumors, an immune suppressive micromilieu and limited in vivo persistence of NK cells. Therefore, this review provides an overview about the NK cell biology, alterations of NK cell activities, changes in tumor cells and the tumor microenvironment contributing to immune escape or immune surveillance by NK cells and their underlying molecular mechanisms as well as the current status and novel aspects of NK cell-based therapeutic strategies including their genetic engineering and their combination with conventional treatment options to overcome tumor-mediated evasion strategies and improve therapy efficacy.